2021
DOI: 10.17977/um044v6i22021p88-96
|View full text |Cite
|
Sign up to set email alerts
|

Edukasi Dengan Media Booklet Terhadap Pengetahuan Gizi Prakonsepsi, Sikap dan Asupan Zat Gizi Makro Wanita Pranikah

Abstract: The prevalence of chronic energy deficiency (KEK) in Jombang District has a percentage of 15.17 percent in women who are not pregnant and 12.63 percent in women of childbearing age who are pregnant (Kemenkes RI, 2018). The high prevalence of chronic energy deficiency (KEK) in women of childbearing age in Jombang District, which exceeds the average in East Java, indicates that there are problems that need special attention. This study aims to analyze the effect of nutrition education with booklet media on preco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
1
0
1
Order By: Relevance
“…According to Wibowo & Suryani, the method of health promotion using pocketbook media affects increasing knowledge of the use of MSG in housewives [9]. The research results of Putri et al, revealed that education using booklet media affected preconception nutrition knowledge, attitudes, and macronutrient intake in premarital women [10]. In line with that, Caesar & Dewi proved that the provision of pocketbook media interventions had a very significant effect on the sanitation knowledge of village health cadres [11].…”
Section: Introductionmentioning
confidence: 90%
“…According to Wibowo & Suryani, the method of health promotion using pocketbook media affects increasing knowledge of the use of MSG in housewives [9]. The research results of Putri et al, revealed that education using booklet media affected preconception nutrition knowledge, attitudes, and macronutrient intake in premarital women [10]. In line with that, Caesar & Dewi proved that the provision of pocketbook media interventions had a very significant effect on the sanitation knowledge of village health cadres [11].…”
Section: Introductionmentioning
confidence: 90%
“…Hal ini diperparah dengan tingginya angka menikah di usia muda dan berkontribusi hingga 35% angka kejadian stunting. Tingginya permasalahan ibu selama masa kehamilan menunjukkan pentingnya gizi prakonsepsi dan dibutuhkan pendidikan gizi dan promosi kesehatan untuk meningkatkan pengetahuan dan perilaku sehat dalam mempersiapkan kehamilan (Putri, Nilna, Ainani, Yuliani, & Sunaryo, 2018). Sebagai salah satu upaya menurunkan angka stunting, maka dibutuhkan peningkatan pengetahuan dan kapasitas pada remaja dan calon pengantin agar dapat mempersiapkan kehamilan yang sehat, salah satunya adalah dengan memberikan kursus persiapan pra nikah (Amalia & Siswantara, 2018).…”
Section: Pendahuluanunclassified